Phenothiazine-based D-A-π-A dyes for highly efficient dye sensitized solar cells: effect of internal acceptor and non-conjugated π-spacer on device performance - Nagane, Satyawan; Ichake, Amol; Agrawal, Ishita; Sadhanala, Aditya; Friend, Richard H.; Ogale, Satishchandra; Wadgaonkar, Prakash P. (ChemPlusChem, 2017)
Three new D-A-pi-A metal-free organic dyes based on phenothiazine as a donor (D) and non-conjugated pi-spacer were designed and synthesized. The incorporation of different 'internal acceptors' (electron traps) such as benzothiadiazole (BTD), benzotriazole (BTA), and pyridine were shown to allow systematic tuning of the energy levels and the photophysical properties. The AI-1 dye showed lower electronic disorder compared with the other two dyes. The efficiencies achieved with AI-1, AI-2, and AI-3 dyes were 8.5% (J(sc) = 15.42 mA cm(-2), V-oc = 0.78 V, FF = 68%), 7% (J(sc) = 12.8 mA cm(-2), V-oc = 0.78 V, FF = 68%) and 6.7% (J(sc) = 11.57 mA cm(-2), V-oc = 0.82 V, FF = 68.26 %), respectively. The incorporation of non-conjugated phenothiazine as a p-spacer in D-A-pi-A dyes showed remarkable enhancement in the photovoltaic performance of dye-sensitized solar cell (DSSC) devices. The sealed DSSC devices with iodide/tri-iodide (I-/I-3(-) @)based liquid electrolyte showed promising stability under ambient conditions.